Age-related Effects on Bilateral Total Knee Arthroplasty: A Comparative Study - Leo Shaw; Han-Ting Shih; Kun-Hui Chen; Cheng-Hung Lee; Kao-Chang Tu (Formosan Journal of Musculoskeletal Disorders)
Background: Patients with advanced age face higher perioperative risks. For patients requiring staged bilateral total knee arthroplasty (TKA), the patient has to face the risks twice. With limited research on the outcomes of simultaneous bilateral TKA in relation to age, this study examined the influence of age on the outcomes and perioperative risks of bilateral TKA. Objectives: This study aimed to assess the influence of age on perioperative risks and outcomes in simultaneous bilateral total knee arthroplasty (TKA), comparing patients aged <75 years to those aged ≥75 years. Materials and Methods: In this retrospective study, a total of 33 patients were enrolled in the study and divided into the elderly group (age <75 years) and the advanced age group (age ≥75 years). The study measured the length of hospital stay, time to mobilization, use of patient-controlled analgesia (PCA), anesthesia type, preoperative and postoperative pain scores, incidence of complications, and comorbidities. Results: Of the 33 patients studied, two age-based groups were identified: the elderly group (age <75 years) with a median age of 68 and the advanced age group (age ≥75 years) with a median age of 79. The elderly group had a significantly higher body mass index and body weight (P < 0.05). No significant differences were noted in anesthesia method, PCA usage, comorbidities, hospital stay duration (6.5 days for elderly and 7.0 days for advanced age), or early ambulation rates. Postoperative pain scores (Visual Analog Scale) increased significantly in both groups (P < 0.05), but preoperative pain and early postoperative pain scores remained comparable between groups. Conclusions: Our study indicates that in healthy patients over 75 years old undergoing simultaneous bilateral TKA, advanced age has minimal effect on clinical outcomes and postoperative complications. However, more extensive research is needed to conclusively determine the impact of advanced age in this setting.